Frequency and specificity of erythrocyte alloimmunization in patients at a reference hospital in Alagoas, Brazil (Research, Society and Development, 2022)
Objective: To determine the frequency and specificity of erythrocyte alloimmunization in patients treated by hemotherapy at the University Hospital Professor Alberto Antunes - UFAL, Maceió-Alagoas, in the period 2013-2018. Methods: Retrospective analysis all patient records with request for red blood cell concentrate (RBC) with a positive erythrocyte antibody test. Results: The incidence of erythrocyte alloimmunization was higher in women n=144 (80.45%) than in men n=35 (19.55%). We detected 13 antibodies, the most frequent specificities identified were anti-D (35.20%), anti-M (12.30%) and anti-E (7.82%). The combination of antibodies occurred in twenty-six cases with prevalence for combinations of antibodies of the Rh system, anti-D + anti-C (23.08%). The highest incidence of alloantibodies was observed in pregnant women. Conclusion: The population studied had high levels of alloimmunization through the Rh System, greater specificity of alloimmunization in women through anti-D and higher rate of alloimmunization among men over the age of 40. Further studies are necessary for a better understanding of red blood cell alloimmunization for population of Alagoas.